Kinetics and thermodynamics study on thiamethoxam adsorption onto TiO2 and perlite supported TiO2 - Ngaha, Emmanuel; Duranoglu, Dilek (SPRINGER, 2025)
Adsorption of thiamethoxam onto TiO2 and perlite supported TiO2 composite (PST) was investigated at different contact time and temperature (295 and 318 K). Adsorption kinetic was evaluated by using the Lindstrom adsorption model to obtain the rate constants of adsorption (k1) and desorption (k2) simultaneously. Thermodynamic parameters of adsorption like activation energy (triangle Ea), Gibbs free energy (triangle Ga), enthalpy (triangle Ha), and entropy (triangle Sa) were also calculated. The adsorption progressively increased with the contact time until equilibrium was achieved, except with PST (295 K), where almost 81% of the THX was eliminated during the initial 10 min. Equilibrium was reached after 35 min for TiO2 and PST at any temperatures. The endothermic nature of the adsorption reaction of THX onto TiO2 and PST has been highlighted. The modeling of the adsorption process allowed us to obtain the theoretical expression of THX adsorbed fraction (phi(t)) and then the adsorption (k1) and desorption (k1) rate constant. Adsorption was faster than desorption and spontaneously occurred, unlike desorption, which was non-spontaneous.
Keywords: Thiamethoxam; Perlite; Titanium dioxide; Adsorption/desorption kinetics; Lindstrom adsorption model; PHOTOCATALYTIC DEGRADATION; GRAPHENE-OXIDE; Chemistry